Hepatic CYP2B10 is highly induced by binge ethanol and contributes to acute‐on‐chronic alcohol‐induced liver injury. (25th October 2022) - Mackowiak, Bryan; Xu, Mingjiang; Lin, Yuhong; Guan, Yukun; Seo, Wonhyo; Ren, Ruixue; Feng, Dechun; Jones, Jace W.; Wang, Hongbing; Gao, Bin
Abstract: Background: The chronic‐plus‐binge model of ethanol consumption, where chronically (8‐week) ethanol‐fed mice are gavaged a single dose of ethanol (E8G1), is known to induce steatohepatitis in mice. However, how chronically ethanol‐fed mice respond to multiple binges of ethanol remains unknown. Methods: We extended the E8G1 model to three gavages of ethanol (E8G3) spaced 24 h apart, sacrificed each group 9 h after the final gavage, analyzed liver injury, and examined gene expression changes using microarray analyses in each group to identify mechanisms contributing to liver responses to binge ethanol. Results: Surprisingly, E8G3 treatment induced lower levels of liver injury, steatosis, inflammation, and fibrosis as compared to mice after E8G1 treatment. Microarray analyses identified several pathways that may contribute to the reduced liver injury after E8G3 treatment compared to E8G1 treatment. The gene encoding cytochrome P450 2B10 ( Cyp2b10 ) was one of the top upregulated genes in the E8G1 group and was further upregulated in the E8G3 group, but only moderately induced after chronic ethanol consumption, as confirmed by RT‐qPCR and western blot analyses. Genetic disruption of Cyp2b10 worsened liver injury in E8G1 and E8G3 mice with higher blood ethanol levels compared to wild‐type control mice, while in vitro experiments revealed that CYP2b10 did not directly promote ethanol metabolism. Metabolomic analyses revealed significant differences in hepatic metabolites from E8G1‐treated Cyp2b10 knockout and WT mice, and these metabolic alterations may contribute to the reduced liver injury in Cyp2b10 knockout mice. Conclusion: Hepatic Cyp2b10 expression is highly induced after ethanol binge, and such upregulation reduces acute‐on‐chronic ethanol‐induced liver injury via the indirect modification of ethanol metabolism. Abstract : In the current study, we fed mice for 8‐weeks with chronic ethanol plus one or three binges and performed microarray on liver samples. Liver cytochrome P450 2B10 (CYP2B10) expression and protein levels were highly induced by binge ethanol. We generated CYP2B10‐knockout mice and found that they exhibit increased levels of liver injury after chronic‐plus‐binge ethanol administration. CYP2B10 plays a protective role in ethanol‐induced liver injury by indirectly increasing ethanol metabolism and altering liver metabolites.